Formation of the teaching content of Mathematics at the profile school with professionally oriented training (Pedagogy of Higher and Secondary Education, 2015)
Tarasenkova N. A., Lovyanova I. V. Formation of the teaching content of Mathematics at the profile school with professionally oriented training.The article analyzes the meaning of the concept «content of education», theoretical approaches to structuring the content of school education and examins the principles of the contentselection. On the basis of the analysis factors which influence the content formation of school Mathematics are defined and components of the content of professionally oriented training of Mathematics are characterized.
Keywords: he contentof education; the principles of selection; the content components; the professionally oriented training